2011
DOI: 10.1111/j.1468-1331.2011.03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Early subclinical cochlear dysfunction in myotonic dystrophy type 1

Abstract: Our study indicates that cochlear impairment in DM1 is present, even in patients without evidence of hearing loss at a standard audiometric analysis. Hence, in the current clinical practice, an assessment of cochlear function by TEOAE recording may be useful in DM1 patients to identify precocious signs of cochlear dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Only two of these patients had diabetes mellitus and as in DM1 studies, neuropathies in DM2 are not correlated with fasting blood glucose or HbA1C or with age at examination. Sensorineural hearing loss was present in some patients, which was in concordance with studies of DM in which hearing defects have been reported as a sign of the disease …”
Section: Discussionsupporting
confidence: 89%
“…Only two of these patients had diabetes mellitus and as in DM1 studies, neuropathies in DM2 are not correlated with fasting blood glucose or HbA1C or with age at examination. Sensorineural hearing loss was present in some patients, which was in concordance with studies of DM in which hearing defects have been reported as a sign of the disease …”
Section: Discussionsupporting
confidence: 89%
“…It is mostly a cochlear sensorineural hearing impairment which may be interpreted as an early presbycusis ( 81 ), well fitting in the interpretation of DMs as premature aging diseases. Similar features of cochlear impairment have also been described in some studies on DM1 patients ( 82 ).…”
Section: Extramuscular Symptomssupporting
confidence: 83%
“…Hearing loss in type 1 Stickler syndrome resembles early-onset presbyacusis, and is strikingly similar to hearing loss in myotonic dystrophy type 1 caused by a mutation in the DMPK gene, which is supposed to interact with the motility of outer hair cells [13]. In Usher type II patients, characterized by a predominantly high-frequency SNHL that is more severe than in Stickler syndrome type 1, a sensory type of cochlear hearing impairment has been [14].…”
Section: Discussionmentioning
confidence: 97%